Perspective sur la prospective - Migué, Jean-Luc (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
Long term forecasting, as popularized by some recent models of the world, appears to be a-scientific from the standpoint of the social scientists. The basis for this radical judgment is threefold: First, structural relations incorporated into these models of the world seldom go further than stating rigid relations between some physical variables and world output. Second, the factual basis on which these relations are built is often not validated by past trends. Finally, the framework within which these models are cast rules out all possibly for the social sciences to contribute to our understanding of the future. Political and economic adaptation mechanisms are excluded. Futurology as developed by some models is based on poor measurement and poor theory.